Formation geological depth image according to refraction and reflection marine seismic data - Verpahovskaya, A. O.; Pilipenko, V. N.; Pylypenko, Е. V. (Geofizicheskiy Zhurnal, 2017)
The possibility of forming of the geological depth image from marine seismic data observed with the method of reflected waves by multiple overlaps and the refracted method by deep seismic sounding was investigated. The difference in the algorithms for the creating of depth image using the finite-difference migration on the field of reflected and refracted waves is shown. Also there is presented the possibility of comparing and generalizing their results. Researches were carried out using the example of seismic data, observed with the method of reflected waves by multiple overlaps and the refracted method by deep seismic sounding in the area of the Azov Sea.